2016
DOI: 10.1186/s12890-016-0236-y
|View full text |Cite
|
Sign up to set email alerts
|

Can fiberoptic bronchoscopy be applied to critically ill patients treated with noninvasive ventilation for acute respiratory distress syndrome? Prospective observational study

Abstract: BackgroundNoninvasive ventilation (NIV) is a cornerstone for the treatment of acute respiratory failure of various etiologies. Using NIV is discussed in mild-to-moderate acute respiratory distress syndrome (ARDS) patients (PaO2/FiO2 > 150). These patients often have comorbidities that increase the risk for bronchoscopy related complications. The primary outcome of this prospective observational study was to evaluate the feasibility, safety and contribution in diagnosis and/or modification of the ongoing treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Due to these potential deleterious complications, the benefits of this technique are not clear [1]. Moreover, while it is easy and feasible to access the lower airways through an endotracheal tube, performing a bronchoscopy in a spontaneously breathing patient can be challenging, although several reports have proved the safety of this technique in patients on NIV or HFOT [39][40][41][42].…”
Section: Diagnosismentioning
confidence: 99%
“…Due to these potential deleterious complications, the benefits of this technique are not clear [1]. Moreover, while it is easy and feasible to access the lower airways through an endotracheal tube, performing a bronchoscopy in a spontaneously breathing patient can be challenging, although several reports have proved the safety of this technique in patients on NIV or HFOT [39][40][41][42].…”
Section: Diagnosismentioning
confidence: 99%
“…A key point when discussing invasive vs. non-invasive tactics in HAP is the feasibility and safety of performing a fiberoptic-bronchoscopy. Several reports show that fiberoptic-bronchoscopy, followed by BAL or mini-BAL, can be conducted in patients with acute respiratory failure and community- and healthcare-acquired pneumonia and is even safer when non-invasive ventilation and high-flow oxygen therapy are applied [3439]. In a landmark trial, Azoulay et al showed that an invasive approach had a similar rate of intubation to a non-invasive approach in non-ventilated, immunosuppressed patients with acute respiratory failure [40].…”
Section: Discussionmentioning
confidence: 99%
“…FOB for clearing airways helps to improve ventilation and oxygen exchange, thereby avoiding intubation [105]. In special circumstances FOB with or without transbronchial biopsy may be needed for differential diagnosis such as cytopathologic analysis in diffuse interstitial infiltrates [106,107]. Other indications are atelectasis, possibility of lung cancer and assessment of the tracheobronchial tree for tracheobronchial rupture/fistula after surgery or chest trauma.…”
Section: Fibreoptic Bronchoscopymentioning
confidence: 99%
“…For that reason, close ABG analysis should be performed and adjustments in NIV settings including FIO 2 should be considered for the maintenance of adequate gas exchange. Other FOB-related complications such as gastric distention, aspiration, fever, pneumothorax and new worsening of pre-existing or new-onset cardiac arrhythmia can be seen, which are seldom clinically important [105,107]. However, it is crucial to perform FOB with expert staff in the ICU under close monitoring, as there may be need for emergency intubation or invasive mechanical ventilation.…”
Section: Fibreoptic Bronchoscopymentioning
confidence: 99%